1997
DOI: 10.1113/jphysiol.1997.sp021923
|View full text |Cite
|
Sign up to set email alerts
|

Colour adaptation modifies the long‐wave versus middle‐wave cone weights and temporal phases in human luminance (but not red‐green) mechanism.

Abstract: 1. The human luminance (LUM) mechanism detects rapid flicker and motion, responding to a linear sum of contrast signals, L' and M', from the long-wave (L) and middle-wave (M) cones. The red-green mechanism detects hue variations, responding to a linear difference of L' and M' contrast signals. 2. The two detection mechanisms were isolated to assess how chromatic adaptation affects summation of L' and M' signals in each mechanism. On coloured background (from blue to red), we measured, as a function of temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
68
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 37 publications
12
68
2
Order By: Relevance
“…Pokorny et al (1993) showed that, for a 570 nm yellow background ¢eld, the red:green ratio in £icker detection was approximately constant with respect to changes in the mean luminance. Stromeyer et al (1997) also showed that the ratio of the long wavelength cone and middle wavelength cone inputs to the luminance mechanism were constant with respect to the change in the spatial and temporal frequencies.…”
Section: (C) Background Stimulimentioning
confidence: 93%
See 2 more Smart Citations
“…Pokorny et al (1993) showed that, for a 570 nm yellow background ¢eld, the red:green ratio in £icker detection was approximately constant with respect to changes in the mean luminance. Stromeyer et al (1997) also showed that the ratio of the long wavelength cone and middle wavelength cone inputs to the luminance mechanism were constant with respect to the change in the spatial and temporal frequencies.…”
Section: (C) Background Stimulimentioning
confidence: 93%
“…It would appear that pupillary responses can be separately driven by both luminance and chromatic stimuli and that, in agreement with psychophysical studies, at lower spatio-temporal frequencies, the sensitivity of pupillary responses to the chromatic mechanism is higher than that for the luminance mechanism. For instance, Stromeyer et al (1995) showed the sensitivity of the chromatic mechanism to be seven times higher than that for the luminance mechanism for detecting a grating at low temporal (1Hz) and low spatial (1 cycle degree 71 ) frequencies.…”
Section: (A) Pupil and Accommodation Responses Evoked By The Isochrommentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] This article addresses the physiological underpinnings of three phenomena, which involve chromatic adaptation and temporal stimulus modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, two temporal filters for red-green grating stimuli have been explicitly reported using Gabor patches [9,10]; a low-pass filter (sustained ), and a second band-pass filter (transient-2 ). There are strong residual achromatic contributions due to the L-and M-cone phase shifts for red-green stimuli [11,12], and this makes it more difficult to separate either of them from the luminance mechanism. Hence, the intermediate band-pass temporal filter (transient-1 ) has never been proposed as underlying detection of diffuse chromatic spots.…”
Section: Introductionmentioning
confidence: 99%